Increase Employee Morale Through Transformational Leadership, Employee Relation, and Work Environment - Larasati, Ayunda Putri; Martono, S (Management Analysis Journal, 2020)
This aims of this study is to determine the effect of transformational leadership, employee relations, and work environment on employee morale on employees of the Department of Trade, Cooperatives, and SMEs Magelang Regency. The type and design of research used in this study is quantitative research. Sampling in this study uses a saturated sampling technique and obtained a sample size that must be used is 130 employees. The analytical method used is the instrument test (validity and reliability), the classic assumption test, and the hypothesis test with the application of SPSS 22. Data collection methods using interviews, questionnaires, and literature studies. The results of this study indicate that three hypotheses were accepted. So it can be seen that transformational leadership has a positive and significant effect on employee morale. Employee relations have a positive and significant effect on employee morale. The work environment has a positive and significant effect on employee morale. Transformational leadership, employee relation, and work environment together has a positive and significant effect on employee morale.